PENGEMBANGAN KARTU “HISTORICAL OF THE BUDDHA” SEBAGAI MEDIA PEMBELAJARAN MATERI RIWAYAT BUDDHA GAUTAMA - Setiawan, Dita; Waluyo, Waluyo; Parsiyono, Parsiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This research was done for media education purposing alike card which Buddha Gautama life story material. This media was made for easily teaching and learning activity students more easily to understanding the material. This research kind is a research and development method using the ADDIE. With process details: 1) analysis, start from face studying, need analysis, and material analysis; 2) design: i.e decision the kind of card, making card design, and choose the materials; 3) development, i.e: making card component using Corel Draw application, testing the product to the members of material and members of media; 4) implementation, i.e: testing the product with limited access to the students of primary school; and evaluation, i.e: grading the product after testing. The development product had to validate by members of the material and members of the media. The percentage of media experts is 70,83 % which shows that the developing media is feasible to be applied as a learning media. Then the percentage of material experts is 86,11% means that the material on the product is proper for students. Based on this research, the writer gets the conclusion that Historical of the Buddha card from material and media is proper to use as media education